Satyrinae (Lepidoptera: Nymphalidae, Satyrinae) ofthe Munchique National Natural Park. Species diversity and altitudinal distribution - PRIETO-M., CARLOS HUMBERTO (Revista Colombiana de Entomología, 2003)
During the months of June 1999 and May 2000, we carried out a preliminary inventory of the Satyrinae fauna that occurs al the Munchique National Park, paying special attention to the mortification and recovery zones. Traps type Van-Someren Rydon was used,  fatten with decomposing fish or fermented banana. The indexes of the diversity of Shanon-Wienner were found in transects according to the Pollard and Yates method, in the same way we found similarity indexes of Jaccard. Hutchenson's method was used to find significant differences among diversity indexes.  Fifty-five species of the subfamily Satyrinae were collected during this study, distributed in 22 genus and 3 tribes. The genera with the greatest number of species were Pedaliodes with 13 and Euptychia with 6. The diversity index for each chosen sector inside the Park was:  El Cóndor ( 1.400 masl) l.84H'; La Playa ( 1.600 masl) J.84H'; La Romelia (2 .600 masl) l.52H ·; Cerro Santana (3.100 masl) l. 7H ', The most abundant species for these sectors were: E. calixta, T. lineata, P. peucestas, P. polusca respectively. Altitudinal distribution data are shown for each genus and species and a comment list of the species reported at the Munchique National Park is included.